2021
DOI: 10.3390/diagnostics11091649
|View full text |Cite
|
Sign up to set email alerts
|

Molecular RNA Correlates of the SOFA Score in Patients with Sepsis

Abstract: The most common scoring system for critically ill patients is the Sequential Organ Failure Assessment (SOFA) score. Little is known about specific molecular signaling networks underlying the SOFA criteria. We characterized these networks and identified specific key regulatory molecules. We prospectively studied seven patients with sepsis and six controls with high-throughput RNA sequencing (RNAseq). Quantitative reverse transcription PCR (RT-qPCR) confirmation was performed in a second independent cohort. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…Using the Sequential Organ Failure Assessment (SOFA) score, Meidert et al compared septic patients with controls to describe molecular networks (58). Criteria included hypoxia, impaired Glasgow Coma Score, circulatory failure, a low platelet count, and increased serum creatinine and bilirubin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Sequential Organ Failure Assessment (SOFA) score, Meidert et al compared septic patients with controls to describe molecular networks (58). Criteria included hypoxia, impaired Glasgow Coma Score, circulatory failure, a low platelet count, and increased serum creatinine and bilirubin.…”
Section: Resultsmentioning
confidence: 99%
“…Scoring systems such as the well-established SOFA score help predict the outcome. Meidert et al used a miRNA and mRNA gene expression to subgroup according to specific SOFA criteria(58). Other classifications include ARDS versus non-ARDS (57).…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Оценка по SOFA, предложенная более 25 лет назад [21], сохраняет несо мненную актуальность при оценке риска летальности [22,23]. Более того, в настоящее время получены свидетельства связи компонентов этой шкалы с нарушениями при сепсисе внутриклеточных сигнальных пу тей, изменениями уровня матричной и митохондриальной РНК [24]. Указывают, что кардиальная подшкала SOFA в первые 24 ч нахождения в ОРИТ может стратифицировать риск летальности у больных с сепсисом и сопутствующими сердечно-сосудистыми заболеваниями, а также при сочетании септического и кардиогенного шока [25].…”
Section: Discussionunclassified
“…We also found that hyperadhesive VWF released during acute traumatic brain injury mediated EVs to active ECs and platelets, thus responsible for consumptive coagulopathy and vascular leakage in the brain and the lung [31,32]. Increased circulating EVs, containing procoagulant, proinflammatory, and prothrombotic factors in their cargo, have been reported to be predictive biomarkers and likely to enhance immunothrombosis in patients with COVID-19 [130][131][132][133][134][135][136]. Hence, VWF tethered EVs (VWF + EVs) may also be involved in COVID-19-associated endotheliopathy and coagulopathy, and a promising diagnostic or prognostic marker.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%